Irisin mitigates osteoporotic-associated bone loss and gut dysbiosis in ovariectomized mice by modulating microbiota, metabolites, and intestinal barrier integrity - Yiran Wang; Huimin Deng; Zhihui Zhang; Hongbo Wu; Xiaofeng Wang; Zhiwen Zhang (BMC Musculoskeletal Disorders)
Abstract Background Osteoporotic bone defects significantly affect patient health and quality of life. The gut-bone axis plays a crucial role in osteoporosis, and disruptions in gut microbiota are linked to systemic inflammation and compromised bone metabolism. Irisin, a myokine, has shown potential in protecting against osteoporosis, but its mechanisms of action on the gut-bone axis remain unclear. This study aimed to investigate the role of irisin in mitigating osteoporotic bone defects by examining its effects on gut microbiota, related metabolites, and intestinal barrier integrity. Methods An osteoporosis model was created using ovariectomized (OVX) mice. The mice were divided into Sham, OVX, and r-irisin groups. Mice in the r-irisin group received intraperitoneal injections of 100 μg/kg irisin twice weekly for five weeks. Bone parameters were analyzed by micro-CT and histological staining. Gut microbiota composition was examined via 16S rDNA sequencing. Intestinal cytokines and barrier proteins were measured using immunohistochemistry and ELISA. Fecal metabolomic profiling was conducted using liquid chromatography-tandem mass spectrometry (LC–MS/MS), and correlations between gut microbiota, metabolites, and bone metabolism markers were evaluated. Results Irisin treatment improved bone mineral density (BMD), bone volume/tissue volume (BV/TV), trabecular bone thickness (Tb.Th), and trabecular number (Tb.N), and reduced trabecular separation (Tb.Sp) in OVX mice. It enhanced new bone formation and collagen deposition. Irisin restored intestinal barrier integrity by increasing tight junction protein expression and reducing inflammatory cytokines in intestinal tissues. It also modulated gut microbiota diversity, reducing Firmicutes and increasing Verrucomicrobiota abundance. Key fecal metabolites, including atractylon (r = − 0.60, P < 0.01) and enterodiol (r = + 0.83, P < 0.01), showed strong correlations with BMD. Conclusion Irisin mitigates osteoporotic bone defects by enhancing bone formation, restoring intestinal barrier integrity, modulating gut microbiota composition, and influencing fecal metabolites. These preclinical findings highlight irisin’s potential to mitigate osteoporosis via the gut-bone axis.